Supervisi Sebagai Upaya Pengawas Untuk Meningkatkan Kinerja Guru Dalam Implementasi Kurikulum Merdeka - Haris Tou (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
The quality of education is a key aspect in the development of a nation. In Indonesia, the implementation of the "Kurikulum Merdeka" in 2020 is a significant step in keeping up with global developments. Amidst this change, teachers play a central role in delivering this curriculum. They need to adapt, integrate technology, and understand the individual needs of students. Educational supervision becomes a crucial tool for enhancing teacher performance, especially in the implementation of "Kurikulum Merdeka." Educational supervision assists supervisors and teachers in collaborating, providing feedback, and identifying areas for improvement. The implementation of "Kurikulum Merdeka" requires oversight that involves various aspects such as teaching, assessment, and the use of information technology. This research uses a qualitative descriptive analysis approach and focuses on how academic supervision contributes to improving teacher performance in the implementation of "Kurikulum Merdeka." The study employs a literature review approach, utilizing previous research as a data source. The research results indicate that intensive and continuous academic supervision, coupled with teacher mentoring, can enhance teacher performance in addressing the challenges of "Kurikulum Merdeka." As a recommendation, there is a need for increased supervision intensity, the development of supervision techniques, and training in differentiated teaching to support teacher performance in implementing "Kurikulum Merdeka." This way, the quality of education in Indonesia can continue to improve.